Exploring the use and perceptions of community parks with engagement activities: a case study of Tokyo, Japan - Min Zong; Shigeto Yanai; Rushi Wang (Frontiers in Sustainable Cities)
IntroductionUrban parks in crowded cities like Tokyo face challenges such as limited space and declining resident participation in park activities. This study examines how participatory events held in community parks affect residents’ park use, satisfaction, and place attachment. The goal is to develop strategies to enhance user participation in parks located in densely populated areas.MethodsThis study focused on three community parks in Toshima Ward, Tokyo. Data were collected from a survey answered by 176 local residents. The research analyzed how residents’ demographic and socioeconomic affect their participation, identified differences in park use motivations between those who joined events and those who did not, and explored how events affected park visits, satisfaction with park facilities, and place attachment.ResultsParticipation varied by age, family size and length of residence. Younger people and families were more likely to participate. Participants tended to use parks for social or family activities. Non-participants tended to choose activities such as walking alone. Participants visited the park more often. They also preferred park features such as rest areas, open space and easy access. Events such as fairs and community meetings encourage more interaction and strengthened residents’ emotional bonds with the parks.DiscussionThe results show that regular participatory events and better park facilities lead to more park visits. They also increase residents’ satisfaction and place attachment to parks. Urban park managers should consider the diverse needs of different user groups and provide a variety of activities for families and young people.